Value-At-Risk: Effective and Accurate Risk Management of China's Stock Index - YU, Yang (2006)
Managing risks has always been an integral part of financial institutions. The financial markets are characterized by a greater uncertainty, which is referable to the increasing volatility of the interest and exchange rate, and to the high fluctuations of the share quotation. At the centre of recent interest of risk management is an approach so called Value at Risk (VaR). In the past few years it has been accepted by both practitioners and regulators as the right way to measure risks. As a result, the concept of Value at Risk (VaR) which originated in the 1980s with investment banks that were attempting to quantify potential losses on their daily trading portfolio-is becoming increasingly popular. With the development of modern capital markets, China has set up its own stock exchange and is still in its infant. In this respect, this dissertation is dedicated to explain how to estimate VaR of Chinese Stock Index by using the there main approaches (EWMA volatility approach, GARCH approach and Historical Simulation), and their own advantages and disadvantages are presented in theory. Then Backtesting is conducted to test which approach is more accurate in VaR estimation.